KAJIAN TEKNIS PENYEDIAAN AIR BERSIH DI DESA OEBOLA LUAR KECAMATAN FATULEU KABUPATEN KUPANG - Elisabeth Ratna; Rista Theedens (Fakultas Teknik Universitas Cenderawasih, 2022)
The availability of clean water in the Oebola village community has not yet been available due to several obstacles, such as the distance of the water source from the residential area has not yet received the service of a clean water distribution system network that makes it easier for the community to obtain clean water to meet their daily needs. This study aims to determine the pattern of clean water consumption, the potential of water sources, the rate of clean water usage in 2020-2030, and strategies to meet the needs of clean water. The research method used in this research is descriptive method. The results of the analysis show that the current use of clean water is 43 liters/person/day less than the standard 60 liters/person/day, there is an adjustment to the limited water use in daily use such as bathing and washing habits. The potential available water sources from the Oetulu spring with a minimum discharge of 1.27 liters/second is smaller than the demand in 2020, which is 2.89 liters/second and in 2030 it is 4.39 liters/second. The strategy to fulfill clean water needs in Oebola Luar village is to provide clean water distribution system network services that make it easier for the community to obtain clean water.